Women anti-mining activists' narratives of everyday resistance in the Andes: staying put and carrying on in Peru and Ecuador. Issue 10 (3rd October 2017) - Jenkins, Katy
Abstract: This article explores the ways in which activism and resistance are incorporated into the everyday lives and practices of rural women in the Ecuadorian and Peruvian Andes, theorising the nature of women's everyday resistance in long running social conflicts. Drawing on research with women anti-mining activists in Peru and Ecuador, the article emphasises that their resistance is rarely concerned with large-scale protests, transnational activism, and the spectacular, but rather depends on daily resistance and resilience in, often fractured, local communities. I explore how rural women make extraordinary circumstances, including facing lawsuits and accusations of terrorism, part of their everyday lives, and how they articulate their resistance and situate it in place through narratives of staying put and carrying on, drawing on emblematic notions of rural livelihoods to challenge large-scale mining developments in their communities.